A STUDY ON HOW LONG AND SHORT SENTENCES SHOW THE STORY’S PACING IN ANTHONY HOROWITZ’S RAVEN’S GATE - I Wayan Sidha Karya; Ida Bagus Adhika Mahardika (SPHOTA: Jurnal Linguistik dan Sastra, 2019)
Long and short sentences affect the reader’s pace of reading story since they have to farce the complexity of the sentences and words used in it. In this study the impact of the use of long and short sentences on the pace of the story as implemented by Anthony Horowitz, a novelist, in his novel Raven’s Gate, is being explored. Especially the researchers looked at what types of long and short sentences were being used in the novel and how they were building up the story line and their effect on the pace of the story. A sentence with the length of up-to fourteen (14) words is considered to be short and the one over 14 words is considered to be long in spite its grammatical form, whether it is simple or complex. The criteria are based on empirical study as mentioned by Casi Newell in the AJE (American Journal Experts) retrieved from https://www.aje.com/en/arc/editing-tip-sentence-length/, that “the average sentence length in scientific manuscripts is 12-17 words,” with JK Rowling—the writer of Harry Potter—who can be considered to be representative of a modern English writer with a general audience, having the average of 12 words. For convenience we take the liberty of taking 14 words for the longest sort sentences and those which have 15 or more words are considered to be long sentences